Didactismo y moralidad en la labor de traducción de Joaquina García Balmaseda (1837-1911) - Pérez Bernardo, María Luisa (Verba hispanica, 2021)
Joaquina García Balmaseda (1837–1911) is a writer who is well known for her contributions to 19th century literature and journalism. Balmaseda was an in-tellectual who manifested, from a young age, a double artistic vocation: literature and translation. She initiated herself into the literary world through local magazines and also through her translations. While there are many references to Balmaseda’s literary production, especially her contributions to women’s magazines, her work as a translator has not been thoroughly studied. The immense number of Balmaseda’s renderings shows not only that translation had a great impact on her work, but also that she popularized many important writers of her time (George Sand, Paul Féval, Alexandre Dumas, Wilkie Col-lins, Charles Dickens, and Mary Elizabeth Braddon, among others). García Balmaseda exercised a very important role as a translator in La Correspondencia de Espana (1860–1925), a magazine with which she frequently collaborated. The immediacy of the works’ translations stands out, as well as the difficulty that resulted from transferring and shortening long works to accommodate them to the press. In these translations, García Balmaseda included her ideological convictions that revealed longstanding traditional views. By omitting passages and modifying the plot of her translations, Balmaseda accommodated these novels and short stories to the “edifying literature” so typical of the age of Isabella II. In most cases, the deletions or changes affect political, moral, and religious issues, as well as expressions contrary to tradition, marriage, family, and national values.
Keywords: 19 st.; cenzorship; cenzura; didacticism; didaktizem; female translators; García Balmaseda, Joaquina; prevajalke; prevajanje; translation